Simple introduction for data analysis using SPSS version 22 - Wan Muhamad Amir Wan Ahmad; Nor Azlida Aleng; Puspaliza Ghazali (Penerbit Universiti Malaysia Terengganu, 2015)
Majority of applied research need a statistical analysis. In this book, the advanced analysis using SPSS software will be introduced in order to help students or researchers in performing the advanced analysis for their bachelor's degree or a higher degree research project. This book also can be used as a guideline in running the statistical tests using statistical analysis tools.